Pelatihan Bantuan Hidup Dasar Sebagai Upaya Peningkatan Kesiapsiagaan Darurat di Sekolah - Mona Hastuti; Rinawati Tarigan; Ismayadi Ismayadi (BADAN PENERBIT STIEPARI PRESS, 2025)
Basic Life Support (BLS) training was conducted at SMK Negeri 1 Percut Sei Tuan to improve students’ knowledge and preparedness in emergency situations. This community service activity aimed to increase understanding of BLS principles and promote emergency readiness within the school environment. The method applied was a mixed approach combining surveys, direct observation, and practical simulation training. Pre-test and post-test assessments measured knowledge improvement, while participant feedback and observation evaluated behavioral changes. Results showed a significant increase in average test scores from 55% to 85%, with 90% of participants responding positively to the training and demonstrating greater confidence in applying BLS techniques. The program effectively enhanced students’ awareness and practical skills, contributing to a safer school environment. Challenges included limited training equipment and initial participant confidence levels, which suggest the need for additional resources and ongoing training. Future development is recommended to include more comprehensive simulation tools, training for teachers as internal trainers, and integration of BLS materials into the school curriculum to sustain long-term impact. This community service successfully empowered the target group to be more responsive and prepared for emergency situations, promoting a culture of safety.